The geopsychology theory of international relations in the 21st century escaping the ignorance trap - Jain, B. M. (Lexington Books, 2021)
"This book explains how geopsychology is different from mainstream international relations theories, arguing that peace and stability in the troubled parts of the world warrants understanding the psychological dispositions of non-state actors and authoritarian regimes"--